A Study on the Application of Virtual Reality Technology in Engish Language Education Relying on Immersive Learning Environments and Interactive Experience Design - Wang, Lixin (Journal of Electrical Systems, 2024)
This study delves into the application of virtual reality (VR) technology in the realm of English language education, with a focus on immersive learning environments and interactive experience design. The primary objective is to explore the efficacy of incorporating VR technology to enhance the English language learning experience for students. The research investigates the potential of immersive learning environments provided by VR technology and the impact of interactive experience design on language acquisition. The study aims to contribute valuable insights into how these technological advancements can revolutionize English language education, offering an engaging and effective approach to language learning. Through a thorough examination of the immersive and interactive aspects of VR technology, the research seeks to provide a foundation for the integration of these technologies into English language education practices, ultimately paving the way for more innovative and engaging language learning experiences.